2021
DOI: 10.1017/dmp.2021.184
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Social Media Use on Practice of COVID-19 Preventive Measures Among Ethiopian Residents: An Online Cross-Sectional Study

Abstract: Background: Infection with coronavirus disease (COVID-19) has become a severe public health issue worldwide. A broad amount of information related to the novel coronavirus (COVID-19) pandemic was disseminated by social media in Ethiopia. To date, there is limited evidence on the influence of social media use for covid-19 related information on covid-19 preventive practice. Therefore, this study aimed to assess the influence of social media use on the practice of COVID-19 preventive measures in Ethiopia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The study also found that social media exposure to COVID-19 information influences preventive attitudes and behaviors. Higher exposure to COVID-19 details on social media was also associated with 2.5 times more chances of having higher risk perception (aOR 2.5; CI 95% 1.3-5.3) [17], [28], [37]. Predictors of preventive action are not only based on social media awareness, but also incorporate the body of health knowledge, skills, and capabilities known as health literacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also found that social media exposure to COVID-19 information influences preventive attitudes and behaviors. Higher exposure to COVID-19 details on social media was also associated with 2.5 times more chances of having higher risk perception (aOR 2.5; CI 95% 1.3-5.3) [17], [28], [37]. Predictors of preventive action are not only based on social media awareness, but also incorporate the body of health knowledge, skills, and capabilities known as health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Social media platforms are comparatively more powerful in spreading such news for many people. Numerous studies found that social media platforms is an effective tools to improve public awareness of public health issues [12]- [17]. On the other hand, detrimental outcomes may arise due to misinformation including intolerance, racism, inequality, and unhealthy behaviors [18].…”
Section: Introductionmentioning
confidence: 99%
“…The median of the nine questions about usage of social media for COVID-19-related information was determined because the cumulative data is not normally distributed. 34 Finally, those who scored higher than the median value were labeled as good users, while those who scored lower were labeled as poor users.…”
Section: Methodsmentioning
confidence: 99%
“…Ahmad & Murad (2020) in their study of how social media were used to spread panic in the Covid-19 pandemic discovered that Facebook was the most used medium in Iraq to spread information about Covid-19. Sadore et al (2021) conducted a similar study in Ethiopia and discovered that exposure to social media messages on Covid -19 had a positive influence on Covid-19 preventive measures uptake leading to social lifestyle changes orchestrated by uptake of the Covid -19 protocols. Smailhodzic et al (2016) showed in their systematic review that social media exposure effected lifestyle changes among their studied subjects (who were patients) in the areas of disease management and control.…”
Section: Literature Review Of the Studymentioning
confidence: 99%